2016
DOI: 10.4163/jnh.2016.49.5.288
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnazin inhibits LPS-induced inflammation and ROS/RNS in raw macrophages

Abstract: Purpose: The aim of this work was to investigate the beneficial effects of rhamnazin against inflammation, reactive oxygen species (ROS)/reactive nitrogen species (RNS), and anti-oxidative activity in murine macrophage RAW264.7 cells. Methods: To examine the beneficial properties of rhamnazin on inflammation, ROS/ RNS, and anti-oxidative activity in the murine macrophage RAW264.7 cell model, several key markers, including COX and 5-LO activities, NO • , ONOO-, total reactive species formation, lipid peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…LPS, a component of bacterial cell walls, activates the TLR-4 on host cells to initiate oxidative stress and inflammatory responses [51]. Reactive oxygen and nitrogen species contribute to LPS-triggered macrophage activation by regulating nuclear transcription factors, including NRF2 [52]. In this study, LPS treatment increased NO generation and iNOS protein expression, demonstrating that LPS induced oxidative stress and the inflammatory response.…”
Section: Discussionsupporting
confidence: 51%
“…LPS, a component of bacterial cell walls, activates the TLR-4 on host cells to initiate oxidative stress and inflammatory responses [51]. Reactive oxygen and nitrogen species contribute to LPS-triggered macrophage activation by regulating nuclear transcription factors, including NRF2 [52]. In this study, LPS treatment increased NO generation and iNOS protein expression, demonstrating that LPS induced oxidative stress and the inflammatory response.…”
Section: Discussionsupporting
confidence: 51%
“…It leads to the generation of pro-inflammatory cytokines within the brain (TNF-α, IL-1β, and IL-6) and activation of peripheral immune cells [6,7,42]. Encouraged by the previous anti-inflammatory effect of RMZ in acute lung injury [41] and the critical role of inflammation in TBI [43,44], next we thought to examine the effect of RMZ on the serum pro-inflammatory cytokines. It has been found that RMZtreated group showed a significant reduction in the serum level of studied pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in a dose-dependent manner as compared to the TBI group.…”
Section: Discussionmentioning
confidence: 99%
“…All LAB reduced iNOS/COX-2 gene expression: among them, MG5048 showed the highest inhibitory activity of iNOS/COX-2 (Figure 2). iNOS/COX-2 is expressed in LPS-activated macrophages and is known to be a factor related to NO production [10]. In addition, Choi et al and Wang et al reported that LAB treatment reduced NO production by decreasing the iNOS/COX-2 expression in LPS-activated cells [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…NO interacts with superoxide anion (•O 2 − ), an anionic radical, to form peroxynitrite (ONOO − ), which is a powerful oxidizing agent and cytotoxic RNS, causing septic shock, brain damage, and local or systemic inflammatory disorders [5][6][7][8]. Additionally, RNS is known to induce iNOS and cyclooxygenase-2 (COX-2) by activating nuclear factor-κB (NF-κB), a pro-inflammatory transcription factor [9,10]. Therefore, it is necessary to maintain homeostasis by regulating oxidative stress through ROS/RNS-related enzymes and transcription factors [2,11].…”
Section: Introductionmentioning
confidence: 99%